(untitled) (International Journal of Engineering and Computer Science, 2015)
The privacy protection between the buyer and the respective seller is a area of concern in the area of digital image procession security domain. From last few decades it has been an area of research for many researchers due to its high equipped prominence protection of information between buyer and seller. The Proposed work presents new approach to transmitting the digital images using a framework named block truncation coding. The proposed block truncation coding framework main approach is to compress the images according to original gray level pixel value in high equipped manner. Addition of BTC pixel value along with the pseudo random number to obtain the encrypted image in an efficient way and then transmits the obtained encrypted image. Finally at the receiver side the compressed pixel value is obtained by using cryptographic key which is done in well equipped manner and latter the original image is obtained successfully by decompressing the decrypted signal using the BTC approach.